Semiotic Analysis of Absurdism Through The Main Character in The Film Trainspotting - Adam Brahimi Cooper; I Nyoman Udayana; Made Detriasmita Saientisna (Pusat riset dan Inovasi Nasional, 2025)
This study is entitled Semiotic Analysis of Absurdism through the Main Character in the Film Trainspotting. The discussion touches upon the concept of absurdism and how it is reflected through signs in the film Trainspotting (1996), directed by Danny Boyle. The film portrays the life of Mark Renton, a heroin addict living in 1990s Scotland, who struggles to find meaning in an indifferent world. This research analysed the denotative and connotative signs that reflect the main character’s struggle with absurdism and how these signs portray the character’s responses to the absurd, whether through escape or rebellion. This study employed Roland Barthes’ (1991) theory of two-level semiotics to analyse the denotative and connotative meanings of signs, and Albert Camus’ (1955) theory of absurdism to interpret the character’s existential responses. This study uses a descriptive qualitative method. Data were collected by watching the film and analysing both verbal and non-verbal signs using Barthes’ semiotic framework. These findings indicate that Trainspotting contains strong elements of absurdism that can be uncovered through semiotic analysis.